2022
DOI: 10.1186/s13054-022-03935-z
|View full text |Cite
|
Sign up to set email alerts
|

Target temperature management following cardiac arrest: a systematic review and Bayesian meta-analysis

Abstract: Background Temperature control with target temperature management (TTM) after cardiac arrest has been endorsed by expert societies and adopted in international clinical practice guidelines but recent evidence challenges the use of hypothermic TTM. Methods Systematic review and Bayesian meta-analysis of clinical trials on adult survivors from cardiac arrest undergoing TTM for at least 12 h comparing TTM versus no TTM or with a separation > 2 °C b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…In this individual patient data meta-analysis of the TTM2 and HYPERION trials, hypothermia at 33 °C was not associated with improved survival or functional outcomes at 3 to 6 months for adult OHCA patients with an initial nonshockable rhythm when compared with targeted normothermia. Our study, along with recent systematic reviews that used traditional and bayesian meta-analyses, [17][18][19] suggests that the current type of temperature control used to induce and maintain hypothermia (ie, target of 33 °C; duration of the intervention of 24 to 40 hours; associated sedation), which has been used over the past 2 decades, does not provide the intended benefit, as shown in landmark trials. 2,3 Of note, the TTM2 and HYPERION studies are not comparable with previous trials, 2,3 as study cohorts were larger, more heterogenous (ie, different initial rhythms or different causes of arrest), and with a more rigorous methodological structure (ie, lower risk of bias).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this individual patient data meta-analysis of the TTM2 and HYPERION trials, hypothermia at 33 °C was not associated with improved survival or functional outcomes at 3 to 6 months for adult OHCA patients with an initial nonshockable rhythm when compared with targeted normothermia. Our study, along with recent systematic reviews that used traditional and bayesian meta-analyses, [17][18][19] suggests that the current type of temperature control used to induce and maintain hypothermia (ie, target of 33 °C; duration of the intervention of 24 to 40 hours; associated sedation), which has been used over the past 2 decades, does not provide the intended benefit, as shown in landmark trials. 2,3 Of note, the TTM2 and HYPERION studies are not comparable with previous trials, 2,3 as study cohorts were larger, more heterogenous (ie, different initial rhythms or different causes of arrest), and with a more rigorous methodological structure (ie, lower risk of bias).…”
Section: Discussionmentioning
confidence: 71%
“…These differences prevented drawing more definitive conclusions regarding the association of hypothermia with measured outcomes in other subgroups of patients. [17][18][19] Our analysis had enhanced statistical power (ie, combination of raw data resulting in larger sample sizes and increased statistical power), improved data quality (ie, verification and standardization of data across studies), the possibility to assess time-to-event outcomes (ie, time to death), flexibility in modeling (ie, adjust for potential confounders at the individual patient level), and detailed subgroup analyses for a better understanding of treatment effect heterogeneity. As such, this individual patient meta-analysis provides the best available evidence regarding the use of hypothermia in the management of OHCA patients with an initial nonshockable rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…While guidelines recommend a target temperature of 32–37.5 °C for at least 24 h after ROSC, there is no set temperature that has been proven to show more benefit over another, and the selection tends to be patient-dependent. A recent Bayesian meta-analysis determined that temperature control at 32–34 °C as compared to temperatures over 36 °C did not lead to more positive neurological outcomes [ 68 ]. Furthermore, a network meta-analysis indicated that hypothermia at 31–36 °C compared to normothermia at 37–37.8 °C did not lead to increased survival rates or better outcomes, and was associated with a greater risk of developing arrhythmias [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Given outcome rate from ICU care of OHCA patients is generally in line in the range of 50–60%, this would translate into an absolute difference of 12–18% (equalling a number needed to treat of between 5 and 9). This may be an unrealistic effect size compared to other post-cardiac arrest interventions, such as targeted temperature management [ 11 ]. Observational data do suggest that the optimal MAP target in a patient with impaired cerebral autoregulation could be as high as 85–90 mmHg [ 12 ].…”
Section: Take-home Messagementioning
confidence: 99%